2017
DOI: 10.3389/fphar.2017.00102
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancerous Potential of Polysaccharide Fractions Extracted from Peony Seed Dreg on Various Human Cancer Cell Lines Via Cell Cycle Arrest and Apoptosis

Abstract: In this study, four homo/heterogenous polysaccharides (HBSS, CHSS, DASS, and CASS) extracted from peony seed dreg with respective molecular weights of 3467, 4677, 229, and 56 kDa were evaluated for anti-cancerous attributes in prostate cancer cells (Pc-3), colon cancer cells (HCT-116), human breast cancer cells (MCF-7), cervical cancer (Hela cells) and human embryonic kidney 293 (HEK 293) cells as control. Among them, CASS and DASS extracted by alkali, consisted of 34.43% Gal, 26.39% Ara, 21.80% Glc and 35.77%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 74 publications
2
33
4
1
Order By: Relevance
“…Previously, our research group studied the thermal and rheology characteristics of plant-derived polysaccharides and their functional properties [ 14 , 23 , 24 , 25 , 40 ], but the study of the thermal and rheological characteristics of mulberry polysaccharides is still in its infancy. We reported the sequential extraction of MLPs with different solvents such as hot buffer, chelating agent, dilute alkali, and concentrated alkali, which led to considerable differences in yield and chemical composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our research group studied the thermal and rheology characteristics of plant-derived polysaccharides and their functional properties [ 14 , 23 , 24 , 25 , 40 ], but the study of the thermal and rheological characteristics of mulberry polysaccharides is still in its infancy. We reported the sequential extraction of MLPs with different solvents such as hot buffer, chelating agent, dilute alkali, and concentrated alkali, which led to considerable differences in yield and chemical composition.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides are a heterogeneous group of carbohydrates that consist of monosaccharide units with glycosidic linkages [ 13 ] with diverse structures and compositions, which can influence various functional properties. It has been reported that polysaccharides have exhibited various biological activities such as anti-tumor, anti-inflammatory, anti-bacterial, and immunologic activity, as well as anti-mutagenic efficacy [ 14 , 15 , 16 , 17 , 18 ]. Moreover, polysaccharides also play an important role as radical scavengers to prevent oxidative damage [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the extraction of peony seed oil, the protein‐enriched by‐product obtained is known as peony seed meal (Zhang et al, ). In the previous studies, peony seed protein hydrolysate was reported with appreciable physicochemical (Shi, Zhang, Sun, Xu, et al, ), antioxidant (Shi, Zhang, Sun, Qu, et al, ), and anticancerous properties (Wei, Ni, Thakur, Liao, Hu, et al, ; Zhang et al, ). Therefore, the economic value of peony seed meal can be realized through bioutilization of protein.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a condition that occurs when abnormal cells in the body proliferate uncontrollably causing normal cells to die (1). To date, cancer remains the primary cause of death in humans worldwide in spite of the advancement in tools for its diagnosis, treatment, and prevention (2).…”
Section: Introductionmentioning
confidence: 99%